Προσβάσεις : μελετήματα - Χατζηγάκης, Παναγιώτης Χρ. (Εκδόσεις των φίλων, 1990)
Νίκος Παππάς -- Νίκος Καββαδίας -- Βιζυηνός -- Κωστής Μεραναίος -- Τσεζάρε Παβέζε -- Εουτζένιο Μοντάλε -- Γκαμπριέλε Ντ΄Αννούντσιο -- Ούγκο Νταλί -- Χένρυ Μούρ -- Σαλβατόρ Νταλί